The concept of experience in Freud and Husserl (Psicologia USP, 2010)
This article aims to clarify Freuds and Husserls conceptions of experience (Erlebnis). By experience it understands generically a fundamental kind of world experience. This subject, although not directly explored by Freud, became necessary for his theory since the discover of the etiology of hysteria at the beginning of the 1890s, by the cathartic method: the concept of traumatic experience. Husserl, otherwise, starting from the philosophical problem of proving the possibility of universal and necessary knowledge, was compelled to fight against the naturalism of ideas, in 1900, and the naturalism of consciousness, in 1913, in both cases with an analysis of (intentional) experiences. I will show that according to the (natural-scientific) freudian approach, the aim consists of providing a metapsychological explanation of the experience, while the (phenomenological) husserlian one intends to describe the structure of the (intentional) experience. Finally, I will point out some main differences between both approaches of this subject.